2012
DOI: 10.1192/bjp.bp.111.093070
|View full text |Cite
|
Sign up to set email alerts
|

Intellectual disability and other neuropsychiatric outcomes in high-risk children of mothers with schizophrenia, bipolar disorder and unipolar major depression

Abstract: Our findings provide epidemiological support for clustering of neuropsychiatric disorders. Further larger epidemiological studies are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
67
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(73 citation statements)
references
References 44 publications
6
67
0
Order By: Relevance
“…16 Although there has been a great deal of interest in deficits in specific domains of cognition in psych otic illness, it is also well established that a general intellectual deficit is often comorbid with psychotic disorders and is a risk factor for such disorders. [60][61][62] Our results suggest that the rs1938526 risk variant of ANK3 is associated with significant and widespread reduction in cortical thickness and grey matter volume across diverse regions of the cortex. The thinning was so extensive that we increased our FDR-corrected threshold from p < 0.05 to p < 0.01 to highlight the regions most affected.…”
Section: Discussionmentioning
confidence: 79%
“…16 Although there has been a great deal of interest in deficits in specific domains of cognition in psych otic illness, it is also well established that a general intellectual deficit is often comorbid with psychotic disorders and is a risk factor for such disorders. [60][61][62] Our results suggest that the rs1938526 risk variant of ANK3 is associated with significant and widespread reduction in cortical thickness and grey matter volume across diverse regions of the cortex. The thinning was so extensive that we increased our FDR-corrected threshold from p < 0.05 to p < 0.01 to highlight the regions most affected.…”
Section: Discussionmentioning
confidence: 79%
“…The first of the studies of mothers of children with ID identified a higher rate of maternal psychiatric disorders in mothers without a previous disorder (Fairthorne et al 2015a). The second (Morgan et al 2012) identified that the children of mothers with chronic schizophrenia, bipolar disorder or unipolar major depression had a higher rate of ID in their children compared to the children of unaffected mothers.…”
Section: Mental Health Psychiatric Disordersmentioning
confidence: 99%
“…Publication of results based on a subsample of children (N=6303) within the current database [4,10] has already seen translation into practice. Our paper in the American Journal of Psychiatry on reproductive pathology in women with severe mental illness found a significantly increased risk of adverse obstetric outcomes in women [4].…”
Section: Data Typementioning
confidence: 99%